English Language Teaching: Challenges and Strategies from the Indian Perspective - Abilasha, R; Ilankumaran, M (International Journal of Engineering and Technology, 2018)
English, an extensively used language of today, has often been mentioned as â€˜global languageâ€™. It is the lingua franca of the current era and the same is taught and learnt as a second language around the world.Â In India, English is used not only for communicative purpose but also serves as a link language for inter-state and intrastate coordination as the nation is found with the great ethnic and linguistic diversity. Though modern technology has started playing a considerable role in imparting and acquiring the language in schools and colleges especially in the small towns and rural areas is rather inadequate and unproductive. The students studying English at school and college level manage to get through the exams without making enough attempts to either understand the language or learn to appreciate the utility of language. This article highlights the significance of using English as a tool to fulfill the interminably increasing requirements of the competitive corporate world. The tasks before educators in the contemporary day ELT and strategies to overcome are considered in this paper. The method by which the learners can put their knowledge into real daily practice is to fulfill their real-world necessities to gain an expertise over the language is emphasized.Â Â